2015
DOI: 10.1002/btpr.2139
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted three-phase partitioning of polyphenol oxidase from potato peel (Solanum tuberosum)

Abstract: Conventional three phase partitioning (TPP) and ultrasound assisted three phase partitioning (UATPP) were optimized for achieving the maximum extraction and purification of polyphenol oxidase (PPO) from waste potato peels. Different process parameters such as ammonium sulfate (NH4)2SO4 concentration, crude extract to t-butanol ratio, time, temperature and pH were studied for conventional TPP. Except agitation speed, the similar parameters were also optimized for UATPP. Further additional parameters were also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
4
17
2
Order By: Relevance
“…The industrial demand for peroxidase is significantly high due to its multitudinous application. However, its high production cost and expensive source is a hindrance in the large scale production of peroxidase . Hence, we channelized our efforts in developing an extraction method which was economical and simple.…”
Section: Utilization Of Food Waste To Produce Value Added Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The industrial demand for peroxidase is significantly high due to its multitudinous application. However, its high production cost and expensive source is a hindrance in the large scale production of peroxidase . Hence, we channelized our efforts in developing an extraction method which was economical and simple.…”
Section: Utilization Of Food Waste To Produce Value Added Compoundsmentioning
confidence: 99%
“…However, its high production cost and expensive source is a hindrance in the large scale production of peroxidase. [20] Hence, we channelized our efforts in developing an extraction method which was economical and simple. Aqueous two-phase system (ATPS) was employed as a clean alternative for the isolation and purification of peroxidase from potato peels.…”
Section: Utilization Of Food Waste To Produce Value Added Compoundsmentioning
confidence: 99%
“…Whereas, it was indicated that animal feed prepared from this kind of waste have low nutritional values . Moreover, many previous studies identify different antioxidant and antimicrobial molecules that can be extracted from PPR . However, the economic feasibility of the extraction processes of these molecules limit their application .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, carried out the dilute H 2 SO 4 hydrolysis of rice hulls at 122°C for 20, 40, and 60 min using 2% dilute H 2 SO 4 at 1:10 solid:liquid ratio and reported that FS concentrations (glucose) were achieved to be 26 g/L for 20 min, 29 g/L for 40 min, and 33.5 g/L for 60 min under the determined conditions. Niphadkar and Rathod were optimized the conventional three phase partitioning (CTTP) and ultrasound‐assisted three phase partitioning (UATTP) conditions for obtaining the extraction and purification of polyphenol oxidase (PPO) from waste potato peels. Their results showed similarity with us that UATPP gives the highest purification fold of 19.7 with 98.3% recovery of PPO at optimized conditions.…”
Section: Resultsmentioning
confidence: 99%